Economic Sanctions and Informal Employment - Ali Moghaddasi Kelishomi; Roberto Nistico (Institute of Labor Economics (IZA), 2023)
This paper examines how economic sanctions affect the allocation of workers across formal and informal employment. We analyse the case of the unprecedented sanctions imposed on Iran in 2012. Employing a difference-in-differences approach, we compare the probability of being employed in the informal sector before and after 2012 for workers in industries with different pre-existing exposure to international trade. Our analysis reveals that, following the sanctions, workers in industries with higher trade exposure are significantly more likely to experience informal employment compared to workers in industries with lower trade exposure. These results remain robust when accounting for potential sorting issues by using an instrumental variable approach. Our findings suggest that the sudden shock to market access caused by the sanctions might have induced a decline in firms' productivity, especially in industries that heavily depend on imported inputs, and therefore an increase in firms' incentives to reduce the costs by shifting their employees to the informal sector. This sheds light on an important margin of labour market adjustment through which sanctions can affect the economy of the target country.
Keywords: E26; F16; F51; O17; 330; economic sanctions; exposure to trade; informal employment; labor reallocation